Planning for offshore oil 1. - Memorial University of Newfoundland. Extension Service (MUN Extension Service, 1979)
Can people be involved in preparing for the impact of oil? To participate people must be informed about the nature of the industry - potential boom and bust situations, the incredible scale, and its impact on traditional industries.